2022
DOI: 10.3389/fimmu.2022.957157
|View full text |Cite
|
Sign up to set email alerts
|

Road testing new CAR design strategies in multiple myeloma

Abstract: A deeper understanding of basic immunology principles and advances in bioengineering have accelerated the mass production of genetically-reprogrammed T-cells as living drugs to treat human diseases. Autologous and allogeneic cytotoxic T-cells have been weaponized to brandish MHC-independent chimeric antigen receptors (CAR) that specifically engage antigenic regions on tumor cells. Two distinct CAR-based therapeutics designed to target BCMA are now FDA-approved based upon robust, sustained responses in heavily-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…The NKG2D system serves an indispensable role in cancer immune surveillance, and NKG2D-ligand is delivered on the surface of glioblastoma cells and radiotherapy is known to induce its expression (31,94). After systemic administration, chNKG2D CAR-T cells moved to the brain tumor site through the blood brain barrier, and no adverse events were reported (95). The results indicated that local tumor irradiation promoted the movement of CAR-T lymphocytes to the tumor site and increased the expression of IFN-γ in a NKG2D-based chimeric antigen receptor construct (chNKG2D) in CAR-T cells.…”
Section: A Preclinical Study Of Natural Killer Group 2-member D (Nkg2...mentioning
confidence: 99%
“…The NKG2D system serves an indispensable role in cancer immune surveillance, and NKG2D-ligand is delivered on the surface of glioblastoma cells and radiotherapy is known to induce its expression (31,94). After systemic administration, chNKG2D CAR-T cells moved to the brain tumor site through the blood brain barrier, and no adverse events were reported (95). The results indicated that local tumor irradiation promoted the movement of CAR-T lymphocytes to the tumor site and increased the expression of IFN-γ in a NKG2D-based chimeric antigen receptor construct (chNKG2D) in CAR-T cells.…”
Section: A Preclinical Study Of Natural Killer Group 2-member D (Nkg2...mentioning
confidence: 99%
“…Altered cellular metabolism also reduces the anti-myeloma effect of standard-of-care agents, e.g., PIs and immunomodulatory drugs (IMiDs). Metabolic changes within the TME further decreases the beneficial anti-myeloma effects of PIs and IMiDs, monoclonal antibodies and cellular immunotherapies ( 14 , 15 , 23 , 36 ). Despite the development of novel anti-myeloma drugs over the past two decades, disease heterogeneity, high-risk disease, early relapse and treatment resistance remain challenges ( 14 , 20 , 22 , 24 , 33 ).…”
Section: Linking Altered Cellular Metabolism To Multiple Myelomamentioning
confidence: 99%
“…Metabolic changes within the TME further decreases the beneficial anti-myeloma effects of PIs and IMiDs, monoclonal antibodies and cellular immunotherapies ( 14 , 15 , 23 , 36 ). Despite the development of novel anti-myeloma drugs over the past two decades, disease heterogeneity, high-risk disease, early relapse and treatment resistance remain challenges ( 14 , 20 , 22 , 24 , 33 ). Moreover, subclonal heterogeneity of PCs evolves alongside disease progression through the selection of genetically and metabolically adapted subclones ( 37 , 38 ).…”
Section: Linking Altered Cellular Metabolism To Multiple Myelomamentioning
confidence: 99%
“…Recent studies have harnessed the power of T-cells engineered to express chimeric antigen receptors (CARs) to treat MM and other hematologic malignancies (56)(57)(58)(59). Barriers following 24 h co-culture.…”
Section: Steroids Impair T Lymphocyte Activation Reduce Helper T-cell...mentioning
confidence: 99%